Desenvolvimento colaborativo de novos produtos: fatores críticos para pme’s de áudio profissional da américa latina - Souza, Bruno de (Universidade do Vale do Rio dos Sinos, 2018)
The current essay presents a case study on the critical factors for collaborative product development on Latin American SME’s of the professional audio segment. It is justified by the economic relevance of SME’s in Brazil, the difficulties they find to innovate, and the lack of studies regarding open innovation and new product development in the context of these organizations. Its main objective was to identify the critical factors on collaborative new product development, verify the adherence of the companies being studied to them, e identify the existing gaps. To achieve this goal, firstly, a review of the literature was made, and was able to identify the best practices in new product development, and the critical factors for collaboration in this process. Secondly, through a documentary research, observation, and semi-structured interviews, data from a Brazilian and an Argentine company was gathered. The analysis of this data allowed the identification of the existing gaps between their structures, processes and practices, and those recommended for successful collaborative new product development. Through this study, it was possible to verify that the main critical factors are power or size of the companies, mutual gains, motivations and strategic objectives, trust, communication, culture, teams, NPD processes, control and support from management, and past experiences. It has been found that the main gaps in these organizations are on the team composition, NPD processes informality, lack of control, and lack of past experiences
Keywords: Desenvolvimento de novos produtos; Inovação aberta; Colaboração; PME’s; Fatores críticos; New product development; Open innovation; Collaboration; SME’s; Critical factors; ACCNPQ::Ciências Sociais Aplicadas::Administração